1987
DOI: 10.1002/pola.1987.080251204
|View full text |Cite
|
Sign up to set email alerts
|

Methanol transport in PMMA: The effect of mechanical deformation

Abstract: The effect of cold work on the transport of liquid methanol in crosslinked PMMA disks has been determined at temperatures from 35–56°C. Deformed samples absorb at fast rates with kinetics that approach those of Fickian diffusion. Undeformed samples sorb at lower rates and the kinetics tend toward those of Case II transport. Shape recovery accompanied swelling in deformed samples. Samples saturated with methanol were desorbed in cyclohexanol. Resorption of desorbed samples showed fast rates for both deformed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…These data can be analyzed by a mass transport model proposed by Harmon et al 40,41 Their model, which accounts for case I, case II, and anomalous transport, was successfully applied to several solvent-polymer systems. [42][43][44] In our case the water transport in irradiated HEMA copolymer can also be successfully analyzed by Harmon et al's model as shown below.…”
Section: Water Transport: Effect Of ␥-Ray Irradiationmentioning
confidence: 99%
“…These data can be analyzed by a mass transport model proposed by Harmon et al 40,41 Their model, which accounts for case I, case II, and anomalous transport, was successfully applied to several solvent-polymer systems. [42][43][44] In our case the water transport in irradiated HEMA copolymer can also be successfully analyzed by Harmon et al's model as shown below.…”
Section: Water Transport: Effect Of ␥-Ray Irradiationmentioning
confidence: 99%
“…It has also been observed that large plastic strains increase the tendency for Case II diffusion [18,19]. Sanopoulo and Stamatialis [20] observed that Case II kinetics occurred for the uptake of a polymer constrained from expansion between two glass plates when the swollen polymer was sufficiently plasticised in order to deform plastically along the penetration axis to overcome the constraints imposed in the thickness direction.…”
Section: Introductionmentioning
confidence: 99%
“…The solid line in the figure indicates the theoretical curve, which approximately agrees with the experimental data for the solvent with different concentrations of CaCl 2 ·2H 2 O. It is based on a mass transport model proposed by Harmon et al 20,21 The model assumes that the mass transport mechanism accounts for the case I, case II, and anomalous sorption. formula is shown below…”
Section: Mass Transportmentioning
confidence: 79%